A Novel Nitrite-Base Aerobic Denitrifying Bacterium Acinetobacter sp. YT03 and Its Transcriptome Analysis - Li, Bin; Lv, Ran; Xiao, Ying; Hu, Wei; Mai, Yuliang; Zhang, Jingwen; Lin, Lan; Hu, Xiaoyong (Frontiers in Microbiology, 2019)
Nitrite in water environment is very harmful to human and aquatic animals. A novel aerobic denitrifying bacterium able to utilize NO2--N as the only nitrogen source was isolated for the purpose of removing nitrite from water, which was identified as Acinetobacter sp. and named to be YT03. The growth and denitrification activity of strain YT03 were assessed comprehensively. Results showed that the nitrite in water with an initial concentration of 10 mg·L-1 could be completely removed within 6 h by strain YT03, and the optimal conditions for strain YT03 to remove nitrite were as follows: sodium succinate as the carbon source, C/N ratio of 16, pH of 6.5, temperature of 30°C, and shaking speed of 250 rpm. An RNA-Seq transcriptome analysis was used to find genes that associated with nitrite removal. Compared with the removal of ammonia nitrogen, 47 genes were significantly differentially expressed, including 20 up-regulated and 27 down-regulated genes, mainly involved in the transport process, biosynthetic process and so on. And among the differentially expressed genes, C4-dicarboxylate transporter (DctA) and nitrate/nitrite transporter (Nrt) might be of importance for the efficient utilization of carbon and nitrogen sources in aerobic nitrite denitrification with sodium succinate by strain YT03.